Group Reference Pengaruh Group Reference Terhadap Pengambilan Keputusan Wisatawan Dalam Mengunjungi Objek Wisata Tetempangan Hill di Kab.Minahasa Prov. Sulawesi Utara - DEISY CHRISTINA ANDIH; Margaretha Nova Warokka (HOSPITALITI DAN PARIWISATA, 2019)
North Sulawesi has a beautiful nature with extraordinary natural wealth. One kind of the natural wealth possessed by the province of North Sulawesi, especially Minahasa Regency, is the Object of Tetempangan Hill. It is a natural tourist’ attraction which presents a very beautiful natural scenery of the expanse of sea and mountains that stretches. . The Tetempangan Hill tourist attraction is located between Koha village and Agotey village. Day by day, more and more tourists visit this attraction both young and old who come to enjoy the existing natural beauty. This research was conducted by using descriptive quantitative method. Descriptive research was done to get description about group reference (X) which becomes independent variable in relation to decision of tourists (Y) as dependent variable. Research was through data obtained from the results of questionnaires, interviews and secondary data of Tetempangan Hill, Minahasa Regency, North Sulawesi Province. Technique of collecting data used was survey method that is collecting data of an object in the field by taking a sample from a population by using questionnaires as a data collection tool spread to 60respondents. In addition, the authors use statistical tests. Group reference, in this case family and friends ,have a significant influence on the decision of the tourists to visit the attraction of Tetempangan Hill ,Minahasa Regency , North Sulawesi Province. Decision making by tourists in visiting the attractions of Tetempangan Hill has a positive relationship with the influence of the group reference ,in this case, family and friends.